Digital control by manipulator of railway track machine. Issue 8 (1st December 2022) - Larkin, Eugene; Privalov, Aleksandr
Abstract: Digital control of manipulator of railway track machine (RTM). It is shown, that exactness and performance of operation execution are the main characteristics, which determine quality of work RTM. Manipulator design with pyramidal structure, in which mechanism is actuated with linear drives, placed in parallel, is described. Mathematical model of exactness evaluation, when there is dry friction at actuators, is worked out. It is shown, that mechanics parallelism leads to cross-links between grasp coordinates control channels. Flowchart of manipulator under investigation, as the object under control, is given. The analytical descriptions of object under control and control algorithm, underlying Von Neumann type controller, are fulfilled with description of delays, linked with features of controller operation, namely operator-by-operator interpretation of algorithm, unfolding in physical time. For estimation of time delays at interface between controller and manipulator semi-Markov model of Von Neumann computer operation is worked out. The method of estimation lags in contours, based on transformation the ergodic semi-Markov model into non-ergodic one, and computation expectations and dispersions of time interval from-point-to-point wandering through semi-Markov process, is proposed.